Eigenvalues, laplacian eigenvalues, and some hamiltonian properties of graphs - Li, Rao (Utilitas Mathematica, 2012)
Using the eigenvalues or Laplacian eigenvalues of graphs, we present several sufficient conditions for some Hamiltonian properties of graphs.